2014
DOI: 10.14738/jbemi.12.146
|View full text |Cite
|
Sign up to set email alerts
|

Temporal decoupling of oxy- and deoxy-hemoglobin hemodynamic responses detected by functional near-infrared spectroscopy (fNIRS)

Abstract: This study provides experimental evidence that there is temporal decoupling between the hemodynamic responses of oxy-and deoxy-hemoglobin (Hb) as detected by functional nearinfrared spectroscopy (fNIRS). Using 64 spatially distributed optrodes to record motor cortical activities during a free arm movement task (right-left and front-back movements), we detected that the temporal profile of oxy-and deoxy-Hb responses are desynchronized and decoupled (i.e., oxy-and deoxy-Hb levels do not rise and fall at the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
0
16
0
2
Order By: Relevance
“…It measures the scattered light through the brain using light-detectors (optodes) positioned 2~4 cm apart from the light-source on the scalp. Typically, the changes of the hemoglobin concentration can be computed, based on the modified Beer-Lambert law (MBLL), according to the known extinction coefficients and differential path-length factor [114]. Recently, this technique has been integrated into portable equipment using light emitting diodes, electronic circuits, and wireless transceivers [8,15].…”
Section: Introductionmentioning
confidence: 99%
“…It measures the scattered light through the brain using light-detectors (optodes) positioned 2~4 cm apart from the light-source on the scalp. Typically, the changes of the hemoglobin concentration can be computed, based on the modified Beer-Lambert law (MBLL), according to the known extinction coefficients and differential path-length factor [114]. Recently, this technique has been integrated into portable equipment using light emitting diodes, electronic circuits, and wireless transceivers [8,15].…”
Section: Introductionmentioning
confidence: 99%
“…Temporal decoupling of HbO and Hb signals indicates that either metric represents only a portion of the hemodynamic response associated with neural processing (Tam and Zouridakis, 2014). Thus, we report primary results for changes in HbO and include results for Hb in the Supplement for completeness (see Supporting Information, Text and Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The parietal cortex, which has previously been implicated in motor planning (Hanakawa et al, 2008) did not show any differences in activation measured by change in HbO during the straight portion (preparatory to making the lane-change maneuver) under incongruent vs. congruent steering control, although we did note a significant difference in Hb signal in the right superior parietal cortex when comparing incongruent to congruent steering (Supporting Information). Lack of significant results for HbO during the preparatory period may be due to the timing of our experimental design and/or temporal decoupling of HbO and Hb signals during motor planning and motor execution (Tam and Zouridakis, 2014). As mentioned previously, considering both HbO and Hb signals is important in the evolving field of fNIRS research (Tachtsidis and Scholkmann, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the necessity for more "fine" research on hemodynamic response's features registered in the NIR modality in order to obtain more detailed description of its features from the point of view of physiology is obvious. In [83], experimental confirmation presented that there is a time difference between hemodynamic answers in oxy-and deoxyhemoglobin. Authors revealed that a time profile of hemoglobin-concentration-change curve is desynchronized; i.e., their levels do not fall, and their sum and the difference do not rise simultaneously.…”
Section: Particular Examples Of Bci On Nirs and Hybrid Bcimentioning
confidence: 99%